[PP.09.15] CHRONIC HEMODIALYSIS CONTRIBUTES TO INCREASED ARTERIAL STIFFNESS AND TO IMPAIRED DIASTOLIC FUNCTION IN PATIENTS WITH END-STAGE RENAL DISEASE AFTER SIXTY MONTHS OF TREATMENT. (September 2017) - Calvez, V.; Palladino, M.; Cesario, V.; Brogna, F.; Fofi, C.; Ciavarella, G.M.; Punzo, G.; Volpe, M.; Savoia, C.
Abstract : Objective: Dialysis may induce vascular stiffness partly through alterations of calcium/phosphate levels. We sought to determine the role of dialytic age (DA) on the indexes of structural alterations in the cardiovascular system. Design and method: We studied 14 patients on chronic hemodialytic therapy. Twenty-four newly diagnosed never treated hypertensive patients and 16 normotensive controls were also studied. The patients on hemodialysis were divided in two groups with respect to the DA: <60-months (DA<60, n = 7) or >60-months (DA>60, n = 7). The levels of calcium/phosphate were evaluated retrospectively on repeated measurements performed after the dialytic treatment over months. After the dialytic treatment, when dry weight was reached, we evaluated peripheral blood pressure (pBP), the parameters derived by tonometric analysis of the pulse waveform (central blood pressure-cBP-, Subendocardial Viability Ratio-SEVR-, carotid-femoral-pulse-wave-velocity-cf-PWV-) and those obtained by echocardiography: ejection fraction (EF-for systolic function) and E/e' (for diastolic function). The ultrafiltration volume was also evaluated. Results: All the groups were similar for sex and BMI, both DA<60 and DA>60 were older than hypertensives and controls (58.33 ± 3.71 and 59.83 ± 7.98 vs 44.14 ± 1.28 and 40.63 ± 2.05 years, respectively, P < 0.05). In both DA<60 and DA>60 calcium/phosphate levels and ultrafiltration volume were similar. pBP was significantly increased and similar to hypertensive patients in DA>60 vs DA<60 (systolic-pBP: 154.2 ± 4.51mmHg vs 132.5 ± 5.18mmHg, P < 0.01 and diastolic-pBP:90.4 ± 49mmHg vs 78.5 ± 3.3mmHg, P < 0.01). cBP was increased and similar to hypertensive patients in DA>60 vs DA < 60 (systolic-cBP: 140.8 ± 8.4mmHg vs 111.2 ± 3.36 mmHg, P < 0.001 and diastolic-cBP: 88.2 ± 3.73mmHg vs 72.33 ± 7.78mmHg, respectively, P < 0.05). cf-PWV was similar in normotensive, hypertensives and DA<60, whereas it was increased only in DA>60 vs the other groups (9.6 ± 1.4m/s vs 6.19 ± 0.28m/s and 7.03 ± 0.22m/s and 7.13 ± 1.4m/s, respectively, p < 0.05). SEVR was similar in all the groups. EF was preserved and similar in all the groups. E/e' was significantly increased in both groups on dialysis vs hypertensives and normotensives, however E/e' was significantly higher in DA>60 vs DA<60 (9.16 ± 1.14 vs 6.96 ± 0.72, P < 0.01). Conclusions: Only patients with DA>60 presented increased aortic stiffness and diastolic dysfunction independently of calcium/phosphate levels. This was associated to higher BP. Hence chronic hemodialytic treatment, particularly after 60 months, may play a putative role for the development of cardiovascular alterations in patients with end-stage renal disease.